Islamic reform in South Asia - Osella, Filippo, Ed; Osella, Caroline, Ed (Cambridge University Press, 2013)
"Discusses contemporary Islamic reformism in South Asia in some of its diverse historical orientations and geographical expressions"--Provided by publisher.